2020
DOI: 10.31344/ijhhs.v5i1.239
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides and Glucose Index as Potential Marker of Metabolic Syndrome

Abstract: Background:Triglycerides and Glucose Index (TyG index), a product from fasting levels of triglycerides and glucose, presented promising results as apotential marker of metabolic syndrome in different ethnicity. However, no such reports are available in our population to date.Objective: To see the effectiveness of ‘Triglycerides and Glucose Index’ to predict metabolic syndromein a Bangladeshi population.Methods: This cross-sectional study was carried out in Department of Biochemistry and Molecular Biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…It may be mentioned that similar studies were done in the same hospital setting to predict metabolic syndrome using 'lipid accumulation product' and 'triglycerides and glucose index', which showed that people having normal weights could be metabolically obese and are at risk of diabetes mellitus or cardiovascular diseases or other related complications. 19,20 Our present study reinforces that individuals should be assessed early and periodically and by using VAI, clinicians can detect metabolic syndrome in a simple way, counsel their patients to consider lifestyle interventions, and thereby prevent a significant amount of morbidity and mortality.…”
Section: Discussionsupporting
confidence: 71%
“…It may be mentioned that similar studies were done in the same hospital setting to predict metabolic syndrome using 'lipid accumulation product' and 'triglycerides and glucose index', which showed that people having normal weights could be metabolically obese and are at risk of diabetes mellitus or cardiovascular diseases or other related complications. 19,20 Our present study reinforces that individuals should be assessed early and periodically and by using VAI, clinicians can detect metabolic syndrome in a simple way, counsel their patients to consider lifestyle interventions, and thereby prevent a significant amount of morbidity and mortality.…”
Section: Discussionsupporting
confidence: 71%
“…The study enrolled 5.110 virtually healthy patients aged from 50 to 84 years (average age (65.9 ± 8.3) years) who formed a placebo group and a group of individuals who were administered with intravenous vitamin D 3 in a dose of 200.000 IU once in the first month of the study. Then, each patient received a single vitamin D 3 dose of 100.000 IU monthly for the entire period of observation, which was 2.5-4.2 years (3.3 27 However, some studies reported that vitamin D 3 can reduce cardiovascular risk and the risk of MS occurrence. 11,22,23 In particular, one such paper studied the effect of vitamin D 3 on the risk profile of MS in women in the postmenopausal period.…”
Section: Research Materials and Methodsmentioning
confidence: 99%
“…However, there is no unequivocal opinion on this issue, and the results of studies are very contradictory: there is evidence of the preventive effect of vitamin D on cardiovascular pathology, 11,[22][23][24] while other studies do not confirm such data. [25][26][27][28] Issues of cardiovascular pathology, in particular, coronary heart disease, lead to changes in blood lipid levels, reflecting increased lipolysis in metabolic syndrome. 29 The study aimed to examine the possible effect of vitamin D 3 on the emergence risk of metabolic syndrome and adverse cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…Proportion of Indonesian people aged >5 years who consume less vegetables and fruit (<5 servings per day a week) is 95.4% 2. Accumulation of fat cells can increase insulin resistance and increase blood glucose 4 . Central fat accumulation and increased of triglycerides often occur in overweight individuals and are one of the causes of prediabetes 1,5 . Increased blood glucose and decreased insulin function can increase sensitive lipase hormone which will cause lipolysis resulting in release of fatty acids and glycerol into the blood circulation.…”
Section: Introductionmentioning
confidence: 99%